ANALISIS RANTAI PASOK DAN MEKANISME IMPOR BERAS DALAM MENJAGA STABILITAS HARGA DI INDONESIA - Veronica, Veronica; Koto, Siti Khadijah; Efendi, Ade Irfan; Suryandari, Mega (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2025)
In January 2024, there was a rice deficit of 2.8 million tons, while rice production in 2023 reached 53.63 million tons of dry milled grain (GKG), down 2.05% from the previous year. The main problem in the supply chain is the role of middlemen who buy rice at low prices and sell it at high prices to traders and consumers. Perum BULOG is advised to buy directly from farmers to overcome this problem. In addition, the supply chain of imported rice involves eight complex stages. The government needs to regulate imports based on the production deficit and increase production through cooperation with the National Research and Innovation Agency (BRIN). The use of 4.0 technology in distribution, such as resource planning and warehouse management systems, is also recommended. However, challenges such as the limited digital infrastructure in remote areas and the lack of farmers' understanding of digital agriculture require special attention. Therefore, government policies must focus on technology procurement, improving human resource competence, simplifying bureaucracy, engaging the private sector, monitoring cartel practices, and mitigating external risks. This comprehensive approach is expected to strengthen food security and ensure rice price stability throughout Indonesia.